On the molecular mechanism of surface charge amplification and related phenomena at aqueous polyelectrolyte-graphene interfaces - Chialvo, A.A.; Simonson, J.M. (Condensed Matter Physics, 2011)
In this communication we illustrate the occurrence of a recently reported new phenomenon of surface-charge amplification, SCA, (originally dubbed overcharging, OC), [Jimenez-Angeles F. and Lozada-Cassou M., J. Phys. Chem. B, 2004, 108, 7286] by means of molecular dynamics simulation of aqueous electrolytes solutions involving multivalent cations in contact with charged graphene walls and the presence of short-chain lithium polystyrene sulfonates where the solvent water is described explicitly with a realistic molecular model. We show that the occurrence of SCA in these systems, in contrast to that observed in primitive models, involves neither contact co-adsorption of the negatively charged macroions nor divalent cations with a large size and charge asymmetry as required in the case of implicit solvents. In fact the SCA phenomenon hinges around the preferential adsorption of water (over the hydrated ions) with an average dipolar orientation such that the charges of the water's hydrogen and oxygen sites induce magnification rather than screening of the positive-charged graphene surface, within a limited range of surface-charge density.